ปัจจัยที่ส่งผลต่อพฤติกรรมการเลือกซื้อคอนโดมิเนียมของประชากร ในย่านบางแค กรุงเทพมหานคร - อุดมแก้ว นฤมล; มณีกูล ฉัตรพล (Journal of Buddhist Education and Research (JBER), 2024)
This research is aimed to study (1) The factors of demographic affecting buying behavior Condominiums (2) The buying behavior of condominiums among the population in Bangkhae area. Bangkok and (3) The factors of Integrated Marketing Communication strategies that affecting buying behavior Condominiums among the population in Bang khae area Bangkok. The sample used for this research was who live in Bangkhae Bangkok, 400 cases by analysis of variance of a sample of 2 groups and multiple regression analysis. The research findings revealed that integrated marketing communication strategies affecting buying behavior of condominiums among the population in Bangkhae area Bangkok at a statistical significance level of 0.05. Is direct marketing, advertising, public relations, sales promotion, and sales by salespeople respectively. The integrated marketing communication strategy in these 5 areas can predict the buying behavior condominiums of the population by 72.20%.